Extracellular Vesicles: A Novel Opportunity for Precision Medicine in Respiratory Diseases - Carnino, Jonathan M.; Hao Kwok, Zhi; Jin, Yang (Frontiers in Medicine, 2021)
Extracellular vesicles are membrane-bound nanoparticles secreted by cells which play a well-known role in cell to cell communication. The most update to date nomenclature categorizes extracellular vesicles based on their relative size, protein markers, and/or the cell type of origin. Extracellular vesicles can be isolated from biological fluids using a variety of methods, including but not limited to, ultrafiltration, size-exclusion chromatography, differential ultracentrifugation, density gradient centrifugation, precipitation-based methods, and immunoaffinity capture. These nanovesicles carry distinct “cargo”, made up of biomolecules such as nucleic acids, lipids, and protein, which is delivered to nearby target cells. The “cargo” profile carried by extracellular vesicles is critical in their role of communication and resembles the physiological status of the cell they originated from. Extracellular vesicle-cargo profiles hold the potential to be used in diagnostic panels for a variety of diseases through a novel method known as “liquid biopsy”. In addition to this, extracellular vesicles may serve as a potential method to deliver drugs to specific cells within the body. This mini-review provides background into what extracellular vesicles are, methods of isolating these nanoparticles, their potential use as a biomarker and drug delivery system for precision medicine, and a summary of the current literature covering the role of some extracellular vesicle-cargo’s in various pulmonary diseases.